BIBLIOMETRIC METHOD AS A TOOL TO PREVENT FRAUD IN THE HOSPITAL ENVIRONMENT: A STUDY OF STRATEGIES, CHALLENGES, AND THEIR IMPACT ON FINANCIAL MANAGEMENT - Soeratin, Harry Z.; Mayuri, Ni Kadek Lila (PT. Altin Riset Publishing, 2025)
This study aims to identify bibliometric methods in fraud prevention in a hospital environment. The research method used was bibliometric analysis. Data were collected from various indexed scientific journals relevant to the topic of fraud in hospitals. The data analysis process involved identifying publication trends, fraud risk patterns, prevention strategies, as well as implementation constraints in the healthcare sector. The results showed that the bibliometric method is effective in mapping fraud-related research trends and prevention strategies. Successfully implemented fraud prevention strategies involve strengthening internal control systems, using information technology to monitor financial transactions in real time, and integrating technological approaches with manual supervision. However, some key challenges, such as technological limitations, lack of human resource competencies, and internal resistance, are still obstacles in the implementation of bibliometric methods. The positive impacts of implementing this method include increased transparency and accountability in hospital financial management, as well as the ability to detect financial anomalies more quickly and accurately. This study provides policy recommendations to strengthen the fraud prevention system through bibliometric methods, staff training, and strengthening information technology.